Menjadi Kota Modern - Makkelo, Ilham Daeng (Masyarakat Sejarawan Indonesia, 2018)
The focus of this paper concerns the idea of ​​a dream as a modern city, especially in Makassar. Started since the beginning of the 20th century, when the cities in Indonesia are in a vortex that blends with the development of global modernity. Even to some extent, the practice is more than what is shown or is happening in the West. The dream of a modern city is knit by one successive regime, always trying to present and translate the spirit of modernity of every age. However, urban planning as one of the aspects of the modern city, on the one hand, gives birth to a reality beyond the plans that have prepared. On the other hand creates irony with the many imbalances or contradictions. In Makassar, urban planning can never be consistently implemented due to diverse constraints. Urban planning cannot survive as a sustainable policy. Each ruling regime has a city plan that is often inconsistent with continuing previous planning. Subsequent policies tend to be partial and not comprehensive. Keywords: dream, modern city, colonial, postcolonial, Makassar